Pengaruh Penambah Eceng Gondok (Eichhornia crassipes) Dan Air Leri Terhadap Produksi Jamur Merang (Volvariella volvaceae) Pada Media BAGLOG - Anggraini, Nana Dwi, Dra. Suparti, M.Si (2015)
Water hyacinth is a weed plant, which contains such nutrients and cellulose, so the water hyacinth is expected to be used as a planting medium mushroom. Leri water contains minerals, vitamins B1, B12, and nutrients are utilized as additional nutrients for the growth of mushroom. The purpose of this study was to determine the effect of water hyacinth and water leri on productivity mushroom on baglog media. This research is compiled using a completely randomized design (CRD) with two factors and three replications. Factor 1 weight hyacinth: (E1) 125 grams, (E2) 250 grams, (E3) 375 grams. Factor 2 leri water volume (L1) and 50 ml (L2) of 100 ml. Parameters measured were body weight of the fruit and the number of mushroom fruit body. Data were tested by analysis of variance 2 lanes. Based on the analysis of variance showed that the addition of water hyacinth and water media leri with different concentrations of influence on the body weight of the fruit and the number of mushroom fruit body. The best treatment for the body weight of the fruit is E1L1 namely 76.67 grams, while the lowest was E3L1 treatment is 60 grams. The best treatment is E1L1 number of fruiting bodies is 7 pieces, while the lowest treatment E3L2 is 3 pieces.